Selkirk Rex - Noelle, Becky (New York, NY : Lightbox Learning Inc., 2024)
Some people say Selkirk rexes are "cats in sheep's clothing" because their long curls look like wool. However, the Selkirk rex is loved for more than its looks. These cats are friendly, loyal, cuddly, and make great family pets. Learn more about Selkirk rex cats and how to take care of them in Selkirk Rex, a Fantastic Cats book
Includes index
Keywords: Rex cat -- Juvenile literature